Indoor Environmental Quality for UKM Architecture Studio: An Analysis on Lighting Performance - Nurakmal, Abdullah@ Goh Tuo Ho; Azalillah Ramdani, Musa; Che-Ani, A. I.; Norngainy, Mohd Tawil; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2012)
Lighting can be efficiently used to maximize occupant comfort, and to conserve energy. This paper focuses on lighting in UKM architecture studio space in order to achieve better IEQ. Good design for building requires sufficient daylight for tasks performed within a space. This is achieved by providing enough means to let in diffused light from the sky, but keep out direct light from the sun to prevent heat gain and glare. Lighting is important to the student because high quality lighting improves student moods, therefore their learning. The artificial light is used most of the time in UKM architecture studio to optimize student vision and comfort. The methodology of the lighting analysis is first by using the equipment named LM-8100, and second by a questionnaire in gauging the lighting comfort level from students’ perspective. Lighting measurement is taken for 11-hours in 2 days for UKM year 3 architecture studio. The finding shows that the lighting setting is not within the range of Malaysian Code of Practice on Indoor Air Quality, but the students perceived it as normal and this is do not hinder them to stay longer inside their studio. This situation will affect the student ability to perceive visual stimuli in short term and health in terms of students' vision in the long run.